Integrated Constructed Wetlands: concept, design, site evaluation and performance. (28th September 2007) - Harrington, R.; Carroll, P.; Carty, A.H.; Keohane, J.; , C. Ryder
'Integrated Constructed Wetlands' (ICW) are a joined-up approach to land and water management. Significant synergies were achieved by explicitly combining environmental, ecological and aesthetic objectives. Intercepted precipitation was found to be the main factor determining treatment efficacy. Soil infiltration and evapo-transpiration combined to enhance hydraulic residence time. A wetland area and configuration were the principal factors determining effluent water quality. During periods of low precipitation ICW discharge tended to positive synchrony with the receiving waters. There were significant improvements to the ecology and water chemistry of receiving waters after five years of ICW intercepting about 75% of farmyard pollution.